2017
DOI: 10.1002/brb3.717
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and cognition: Pupillary responses to problem‐solving in early multiple sclerosis patients

Abstract: IntroductionIn early multiple sclerosis (MS) patients, cognitive changes and fatigue are frequent and troublesome symptoms, probably related to both structural and functional brain changes. Whether there is a common cause of these symptoms in MS is unknown. In theory, an altered regulation of central neuropeptides can lead to changes in regulation of autonomic function, cognitive difficulties, and fatigue. Direct measurements of central neuropeptides are difficult to perform, but measurements of the eye pupil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…We furthermore observed that higher levels of need for recovery were associated with larger ACA, BPD and DV1 (SCREEN condition) values, suggesting larger PNS activation. This result is in line with the previous finding that people with higher levels of fatigue and need for recovery tend to show smaller pupil dilation during cognitive tasks, reflecting reduced PNS inhibition [ 51 , 74 ].…”
Section: Discussionsupporting
confidence: 92%
“…We furthermore observed that higher levels of need for recovery were associated with larger ACA, BPD and DV1 (SCREEN condition) values, suggesting larger PNS activation. This result is in line with the previous finding that people with higher levels of fatigue and need for recovery tend to show smaller pupil dilation during cognitive tasks, reflecting reduced PNS inhibition [ 51 , 74 ].…”
Section: Discussionsupporting
confidence: 92%
“…Fourthly, the same scales were used to assess cognitive status in our follow‐up studies and learning effects could not be avoided. Last but not least, fatigue is found to be associated with cognition in many diseases such as post‐stroke and multiple sclerosis (de Rodez Benavent et al, ; Lagogianni, Thomas, & Lincoln, ), but we did not evaluate the fatigue in ESRD patients in our study. More efforts should be made to clarify the relationship between cognition and fatigue in the future study.…”
Section: Discussionmentioning
confidence: 87%
“…The degree of pupillary constriction during a task is a validated biomarker for fatigue and alertness. 27,28 Research has consistently shown that during conditions of fatigue, baseline pupil diameters are smaller than normal. [29][30][31][32][33] Reduction in pupil size by 1 mm has been associated with signs of tiredness.…”
Section: Introductionmentioning
confidence: 99%